Long non-coding RNA DUXAP8 elevates RCN2 expression and facilitates cell malignant behaviors and angiogenesis in cervical cancer via sponging miR-1297 - Jihui Gu (BMC, 2021)
Abstract Background Cervical cancer (CC) endangers women’s health in the world range. Accumulating studies have revealed the crucial regulatory role of long non-coding RNAs (lncRNAs) in multiple malignancies, including CC. Our study aimed to explore the role of lncRNA double homeobox A pseudogene 8 (DUXAP8) in cervical carcinogenesis. Methods Gene expressions in CC were assessed by RT-qPCR. Function experiments and tube formation assays were performed to evaluate the role of DUXAP8 in CC cells. Subcellular fractionation and FISH assays were conducted to determine the subcellular location of DUXAP8. Luciferase reporter, RNA pull down and RIP assays were conducted to investigate the mechanism of DUXAP8. Results DUXAP8 was notably upregulated in CC cells. Downregulation of DUXAP8 repressed cell malignant behaviors and angiogenesis in CC. Mechanically, DUXAP8 boosted the expression of reticulocalbin-2 (RCN2) through relieving the binding of miR-1297 to RCN2 3’-UTR. Moreover, miR-1297 inhibition and RCN2 overexpression could counteract the inhibitory effects of DUXAP8 knockdown on the malignant phenotypes of CC cells. Besides, enhanced RCN2 expression restored the tumor growth in vivo that was inhibited by DUXAP8 repression. Conclusions DUXAP8 promotes malignant behaviors in CC cells via regulating miR-1297/RCN2 axis. Graphical Abstract